Determination of Toxic Heavy Metal Contents of Some Selected Tropical Fruits Grown in Industrial Areas of Bangladesh (Dhaka University Journal of Science, 2022)
Fourteen tropical fruit items were collected from different industrial sites of the Dhaka and Chattogram region, Bangladesh todetermine toxic heavy metal contents. This study aimed at the assessment of the distribution of heavy metals (As, Pb and Cr) as wellas comparison of their level among different locations. The fruit items were analyzed for the quantiﬁcation of the selected heavymetals using Atomic Absorption Spectrophotometer (AAS). The range of lead, chromium and arsenic in the fruit items were 1.12± 0.077 to 2.899 ± 0.013, 0 to 0.217 ± 0.005 and 0 to 0.078 ± 0.002 mg kg-1 respectively. It was revealed from the results that thelevel of toxic metals (As, Cr) in almost all fruit samples were within tolerable limit whereas the level of Pd in all of the fruit samplesexceeded the acceptable limits of WHO standard value. It was also observed from the results obtained that the concentration of themetals found in the samples from Dhaka regions were considerably higher than that of Chattogram. These metal contributors mainlyarising from anthropogenic sources including industrial wastes, automobile emissions, use of fertilizers, pesticides and herbicides inagriculture, paints, sewage and waste disposal. The extended level of these metals causing environmental pollution is hazardous sinceplants accumulate them. Subsequently, crops uptaking these heavy metals consumed by humans and animals which is detrimental tohealth. It is therefore very important that necessary actions need to be taken to monitor the level of these deleterious elements in foodplants. In decision making, planning and risk assessing this present study will play significant role.Dhaka Univ. J. Sci. 70(1): 22-27, 2022 (January)